METODE PENGUKURAN SUDUT GONIAL ANTAR POLA VERTIKAL SKELETAL PADA SEFALOMETRI LATERAL - Putri, Areta Salim Andri; Zen, Yuniar (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2022)
Background: Gonial angle is one of the angles measured in vertical skeletal analysis using lateral cephalograms. Gonial angle is made of tangent line to the posterior border of mandibular ramus with mandibular plane. Definition of gonial angle depends on mandibular plane which generally consists of various methods according to Downs, Tweed, and Steiner.  Purpose: To investigate the difference of gonial angles measurement methods among vertical skeletal patterns on lateral cephalograms. Methods: Observational analytic research was conducted on 21 lateral cephalograms of orthodontic patients who had come to one of orthodontic clinic in Solo in 2016-2021. The cephalograms were taken by the same operator using Vatech PaX-i3D™, then they were categorized into 3 vertical skeletal pattern groups. Reference points and tracings were submitted to supervising orthodontist via ZOOM twice daily in the morning and in the afternoon. The measured data was recorded in table and was analyzed with Statistical for Social Science (SPSS) program. Results: In each vertical skeletal pattern groups, there was no significant difference found among Downs’s, Tweed’s, and Steiner’s gonial angles. There was significant difference among gonial angles of hypodivergent, normodivergent, and hyperdivergent samples. Conclusion: There was no significant difference of three gonial angle measurement methods among three vertical skeletal patterns on lateral cephalograms.